Isocyanate Reduction by Epoxide Substitution of Alcohols for Polyurethane Bioelastomer Synthesis - Arnold A. Lubguban; Zuleica R. Lozada; Yuan-Chan Tu; Hongyu Fan; Fu-Hung Hsieh; Galen J. Suppes (International Journal of Polymer Science)
A phosphate ester-forming reaction was carried out by mixing epoxidized soybean oil with up to 1.5% o-phosphoric acid. In situ oligomerization took effect almost instantly producing a clear, homogeneous, highly viscous, and a low-acid product with a high average functionality. The resulting epoxide was used as a reactant for urethane bioelastomer synthesis and evaluated for rigid foam formulation. Results have shown that with a number of catalysts tested phosphoric acid significantly enhances a solvent-free oxirane ring cleavage and polymerization of the epoxidized soybean oil via phosphate-ester formation at room temperature. The resulting phosphoric acid-catalyzed epoxide-based bioelastomer showed an 80% decrease in extractable content and increased tensile strength at the same isocyanate loading relative to the noncatalyzed epoxide. The oligomerized epoxidized soybean oil materials exhibited ASTM hydroxyl values 40% less than the nonoligomerized starting material which translates to reduced isocyanate loadings in urethane applications.